VALIDITY OF ICT BASED ON INTEGRATED STEM EDUCATION TEACHING MATERIALS TO IMPROVE DATA LITERATURE AND TECHNOLOGY PHYSICS STUDENTS - Liza Marlina; Asrizal Asrizal (Universitas Negeri Padang, 2022)
The development of the 21st century demands changes in resources of human of “broad insight, critical thinking, and literacy” to deal with the development of 21st century education. Conditions in the field found that STEM, data literacy and technology had not been implemented, and the average score of students in physics learning had not been implemented. One solution that can be conducted is to develop ICT materials of teaching on work and energy based on STEM Education. This study aims to determine the validity of ICT-based business and energy teaching materials to integrate STEM Education to improve data and technology literacy of high school students.The research conducted includes development research using the development model of Plomp. The development model of Plomp is carried out until the design and prototype stages, namely determining the validity of the product carried out by experts on the product being developed. The results of the study obtained that the assessment of teaching materials was valid on five components based on data analysis using Aiken, V obtained the results for material substance with a value of 0.77, visual communication display with a value of 0.78, learning design with a value of 0.78, software usage with a value of 0.63 and STEM assessment with a value of 0.74. Based on this validity assessment, it can be concluded that ICT-based business and energy teaching materials integrate STEM Education to improve data literacy and valid high school students' technology so that they can be applied to students in learning